Differential regulation of endothelium behavior by progesterone and medroxyprogesterone acetate - Cutini, Pablo Hernan (2013)
Medroxyprogesterone acetate (MPA) is a synthetic progestin commonly used in hormone replacement therapy (HRT). The aim of this work was to study and compare the effect of progesterone (Pg) and MPA, on the regulation of cellular events associated with vascular homeostasis and disease. Platelet adhesion to endothelial cells (ECs), nitric oxide (NO) production, and cell migration were studied using murine endothelial cells in vitro exposed to the progestins. After seven minutes treatment, MPA significantly inhibited NO synthesis with respect to control value; meanwhile Pg markedly increased vasoactive production. In senile ECs, the stimulatory action of Pg decreases; meanwhile MPA maintained its ability to inhibit NO synthesis.The presence of RU486 antagonized each steroid action. When ECs were preincubated with PD98059 (MAPK inhibitor) or chelerythrine (PKC inhibitor) before Pg or MPA treatment, the former totally suppressed the steroid action, but the PKC antagonist did not affect NO production. In the presence of a PI3K inhibitor (LY294002) a partial reduction in Pg effect, and a reversal of MPA action was detected. Using indomethacin the contribution of cyclooxygenase (COX) pathway was also detected. On platelet adhesion assays, Pg inhibited and MPA stimulated platelet adhesion to ECs. Under inflammatory conditions, Pg prevented platelet adhesion induced by lipopolysaccharide (LPS); meanwhile MPA potentiated the stimulatory action of LPS. Finally, although both steroids enhanced ECs migration, MPA exhibited a greater effect. In conclusion the data presented in this research provide evidence of a differential regulation of vascular function by Pg and MPA